Assessing Primary Care Contributions to Behavioral Health: A Cross-sectional Study Using Medical Expenditure Panel Survey - Anuradha Jetty; Stephen Petterson; John M. Westfall; Yalda Jabbarpour (SAGE Publishing, 2021)
Objectives To assess primary care contributions to behavioral health in addressing unmet mental healthcare needs due to the COVID-19 pandemic. Methods Secondary data analysis of 2016 to 2018 Medical Expenditure Panel Survey of non-institutionalized US adults. We performed bivariate analysis to estimate the number and percentage of office-based visits and prescription medications for depression and anxiety disorders, any mental illness (AMI), and severe mental illness (AMI) by physician specialty (primary care, psychiatry, and subspecialty) and medical complexity. We ran summary statistics to compare the differences in sociodemographic factors between patients with AMI by seeing a primary care physician versus those seeing a psychiatrist. Binary logistic regression models were estimated to examine the likelihood of having a primary care visit versus psychiatrist visit for a given mental illness. Results There were 394 023 office-based visits in the analysis sample. AMI patients seeing primary care physician were thrice as likely to report 1 or more chronic conditions compared to those seeing psychiatrist. Among patients with a diagnosis of depression or anxiety and AMI the proportion of primary care visits ([38% vs 32%, P  < .001], [39% vs 34%, P  < .001] respectively), and prescriptions ([50% vs 40%, P  < .001], [47% vs 44%, P  < .05] respectively) were higher compared to those for psychiatric care. Patients diagnosed with SMI had a more significant percentage of prescriptions and visits to a psychiatrist than primary care physicians. Conclusion Primary care physicians provided most of the care for depression, anxiety, and AMI. Almost a third of the care for SMI and a quarter of the SMI prescriptions occurred in primary care settings. Our study underscores the importance of supporting access to primary care given primary care physicians' critical role in combating the COVID-19 related rise in mental health burden.